Pengujian Black Box pada Sistem Informasi Penjualan HI Shoe Store Menggunakan Teknik Equivalence Partitions - Adella Rosalina; A A Gede Rai Rassi; Gozali Yusuf Hadi; Rizki Ubaidillah; Teti Desyani (Jurnal Informatika Universitas Pamulang, 2020)
Testing software that is incomplete and ineffective can cause various problems that cause losses, especially for users, this test is carried out to ensure that if it does not match what is expected then the system fails. The sales information system at the Hi Shoe Store is then carried out using the Black Box test based on Equivalence Partitions, so it will be known weaknesses in the information system after testing. The system test results show that testing can improve quality and guarantee error free.